Adenovirus-mediated Expression and Packaging of Tissue-type Plasminogen Activator in Megakaryocytic Cells - Chuang, Joseph L.; Schleef, Raymond R. (Thrombosis and Haemostasis, 2001)
Platelets release large quantities of plasminogen activator inhibitor 1 (PAI-1) that plays an important role in maintaining the integrity of fibrin-rich thrombi. In addition, tissue-type plasminogen activator (t-PA), a key physiological regulator of fibrinolysis, has been detected in platelet α-granules at low abundance. This information raises the possibility of enhancing t-PA expression in megakaryocytes as a means to enhance the fibrinolytic properties of platelet α-granules and target PAs directly to fibrin clots. This study was initiated to investigate adenovirus (Ad)-mediated expression and packaging of t-PA into α-granules-like structures in the megakaryocytic cell line MEG-01. Ad/t-PA infection of phorbol myristate acetate (PMA)-differentiated MEG-01 cells increased cellular t-PA levels by 120 fold (1580 ± 130 ng/106 cells at 5 MOI) in comparison to non-or Ad/β-gal-infected cells. Fluorescence-activated cell sorter (FACS) analysis indicates that Ad/t-PA-infected cells yielded a homogenous shift in the t-PA staining profile with a 4-fold shift in mean fluorescence in comparison to non- or Ad/β-gal-infected cells. For the isolation of α-granule-like structures, MEG-01 cell homogenates were fractionated by differential centrifugation and two consecutive Percoll density gradients. Fibrin autography of storage granules revealed a prominent lytic zone at Mr 66 kD comigrating with free t-PA. Quantitative analyses indicate that a 16-fold elevation in t-PA antigen within storage granules in comparison to non- or Ad/β-gal-infected cells. To document the ability of t-PA to be stored in a rapidly-releasable form in these cells, we isolated platelet-like particles from the supernatant of differentiated cells and determined that particles from Ad/t-PA-infected cells display a 4-8 fold enhanced secretion of t-PA following treatment with the classical secretagogue calcium ionophore 23187, ADP, or thrombin. Confocal immunofluorescence microscopy analysis indicates that Ad/t-PA mediated productive expression of t-PA in murine megakaryocytes. These data provide support for the concept of increasing the expression of t-PA in megakaryocytes as a means to alter the hemostatic properties of α-granules.Abbreviations: Ad, Adenovirus; t-PA, tissue-type plasminogen activator; PAI-1, plasminogen activator inhibitor 1; PMA, phorbol myristate acetate; ELISA, enzyme-linked immunosorbent assay; CM, conditioned media; vWF, von Willebrand factor; ECL, enhanced chemiluminescence; PA, plasminogen activator.
Keywords: Tissue-type plasminogen activator; plasminogen activator inhibitor I; platelets; Percoll; megakaryocytes; storage granules; gene transfer; subcellular fractionation; fibrinolysis